Comparative study between high-fidelity simulation and medium-fidelity simulation in decision-making of nursing students: experimental study - Hugo Miguel Santos Duarte; Joana Antunes Castanheira; Ana Sofia Ferreira Pereira; Ângela Pragosa; Edna Tatiana Prazeres Santos; Maria dos Anjos Dixe (Universidade de São Paulo, 2024)
Abstract Objective: to compare the decision-making of Nursing students, before and after theoretical training on basic life support, using the practice of high-fidelity simulation and medium-fidelity simulation. Method: an experimental study was developed, pre- and post-test type, with quantitative, descriptive and inferential analysis, with theoretical training on basic life support and clinical simulation practices, and with evaluation of knowledge and decision-making of Nursing students, at three different moments - before the simulation scenario (T0), after the simulation scenario (T1) and after clinical teaching (T2). Results: 51 students participated in the research, with an average age of 20.25±3.804, of which 92.2% were female. Statistically significant differences (F=6.47; p=0.039) were evident regarding the definition of the problem and development of objectives in decision-making in the experimental group. Conclusion: Nursing students demonstrate an adequate level of knowledge and a good decision-making process, based on the most current instruments produced by scientific evidence, in clinical simulation scenarios in basic life support, and this innovative methodology should be deepened in the Nursing teaching.